(untitled) (Orinoquia, 2026)
The effect of four hydroponic substrates on the growth kinetics, biomass accumulation, and essential oil yield of Plectranthus amboinicus (Lour.) Spreng. was evaluated under tropical conditions in Puerto López, Colombia. A completely randomized design was used with four treatments: river sand (T1), coconut fiber + rice husk mixture 1:1 (T2), rice husk (T3), and pure coconut fiber (T4), with five replicates. Height growth fitted a logistic model (R2 > 0.99), and T2 and T4 showed the highest maximum growth rates (5.88 and 5.53 cm/week). At the end of the cycle, T4 recorded the highest total fresh biomass (880.00 g/plant), fresh leaf biomass (554.22 g/plant), and dry leaf biomass (66.62 g/plant). The highest essential oil yield obtained by microwave-assisted hydrodistillation was observed in T4 (0.748 % on a dry basis; 0.090 % on a fresh basis), followed by T2 (0.577 %), T3 (0.434 %), and T1 (0.320 %). Under the evaluated conditions, coconut fiber favored biomass accumulation and essential oil yield, making it a promising substrate for tropical hydroponic systems of P. amboinicus.